A massive ovarian cyst masquerading as malignancy in unrecognised primary hypothyroidism - Sandhya, S.S.; Praveen, K.D.; Dhananjaya, S.R.; Shivaraj, G. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
We report here probably a huge ovarian cyst of size 7.9x16.4x23 cms which regressed on thyroxine therapy with severe autoimmune primary hypothyroidism in a young woman. It is necessary to consider hypothyroidism and other endocrine disorders in the differential diagnosis of adult patients with ovarian multiple cyst formation in order to prevent inadvertent ovarian surgery.